2017
DOI: 10.1177/1539449217741136
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the 32-item Fitness-to-Drive Screening Measure

Abstract: The Fitness-to-Drive Screening Measure (FTDS) enables proxies to identify at-risk older drivers via 54 driving-related items, but may be too lengthy for widespread uptake. We reduced the number of items in the FTDS and validated the shorter measure, using 200 caregiver responses. Exploratory factor analysis and classical test theory techniques were used to determine the most interpretable factor model and the minimum number of items to be used for predicting fitness to drive. The extent to which the shorter FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Specifically, we determined that although over 43,000 users have accessed the FTDS, they failed to spend the recommended 20 min to complete the FTDS. To overcome this issue, our research team recommended decreasing the completion time of the FTDS by reducing the number of items, thus, the FTDS underwent item reduction (26). Using classical test theory rather than item response theory, the 54-item FTDS was reduced to a 32-item version.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we determined that although over 43,000 users have accessed the FTDS, they failed to spend the recommended 20 min to complete the FTDS. To overcome this issue, our research team recommended decreasing the completion time of the FTDS by reducing the number of items, thus, the FTDS underwent item reduction (26). Using classical test theory rather than item response theory, the 54-item FTDS was reduced to a 32-item version.…”
Section: Introductionmentioning
confidence: 99%
“…Using classical test theory rather than item response theory, the 54-item FTDS was reduced to a 32-item version. Validity testing of the 32-item FTDS indicated excellent concurrent validity with the 54-item FTDS ( r = 0.99) (26). ROC curve results indicated the 32-item version could correctly discriminate between drivers who passed or failed the on-road assessment (AUC = 0.75, p < 0.05, 95% CI [0.65, 0.84]; Medhizadah, Classen, & Johnson, submitted).…”
Section: Introductionmentioning
confidence: 99%
“…A shorter FTDS has been proposed and constructed to overcome the lengthy (and potentially problematic) completion time. The psychometric properties of the 32-item measure look promising as it correlates well with the original FTDS measure (Medhizadah et al, 2018). Establishing the validity of the 32-item FTDS will be the first step toward empirically establishing the measure's potential to differentiate between older drivers who would pass or fail an on-road assessment.…”
Section: Introductionmentioning
confidence: 98%
“…These researchers suggested that decreasing the time needed to complete the measure may potentially increase the utility of the FTDS. Medhizadah et al (2018) constructed a shorter 32-item FTDS that may decrease completion time and potentially increase utilization of the FTDS as per its original intent. This 32-item FTDS demonstrated excellent factorial validity (as illustrated by an exploratory factor analysis) and internal consistency reliability for each factor (Cronbach's alpha = 0.96, 0.88, 0.88).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation